Mexican organized crime and the illegal trade in totoaba maw - Martínez, Israel Alvarado (Trends in organized crime, 2021)
The convergence between wildlife trafficking and other serious crimes has received increasing attention within criminological studies. The present study examines how and why Mexican organized crime groups, in particular drug cartels, have shifted their operations from drug trafficking into specific parts of the illegal trade in totoaba maw. By drawing upon literature research, semi-structured interviews and official documents of the Mexican state, empirical data indicate that Mexican organized crime groups may infiltrate into the poaching and smuggling of totoaba maw as a result of a diversification process, influenced by the social context in which these groups operate. The different interactions between actors involved along the supply chain revealed that organized crime groups adapt to new illicit markets by means of corruption and violence; by establishing alliances with local fishermen and Asian criminal networks along the trafficking chain; by using their existing routes and concealment methods. Finally, in the light of this empirical evidence that infers the complexity of crime convergence, we suggest the introduction of a National Environmental Task Force in Mexico.